Novel anti-biofouling light-curable fluoride varnish containing 2-methacryloyloxyethyl phosphorylcholine to prevent enamel demineralization - Jae-Sung Kwon (Nature Portfolio, 2019)
Abstract We evaluated the efficacy of light-curable fluoride varnish (LCFV) that contains 2-methacryloyloxyethyl phosphorylcholine (MPC) in terms of anti-biofouling properties and prevention of tooth enamel demineralization. MPC was mixed with and incorporated into LCFV at 0 (control), 1.5, 3.0, 5.0, 10.0, 20.0, and 40.0 weight percentage (wt%). Addition of high wt% of MPC resulted in increased film thickness and decreased the degree of conversion, indicating loss of the advantageous properties of LCFV. Addition of 1.5, 3, or 5 wt% MPC significantly reduced the amount of bovine serum albumin adsorbed from a solution and proteins adsorbed from brain heart infusion medium compared to the control (P < 0.001). A similar pattern was observed for bacterial adhesion: significantly less Streptococcus mutans cells adhered on the surface of LCFV with 1.5, 3, or 5 wt% MPC (P < 0.001) than on the control, and similar results were obtained for Actinomyces naeslundii and Streptococcus sanguinis adherence to LCFV with 3 wt% MPC. Finally, bacterial adhesion, surface microhardness loss, and the depth of demineralization were substantially lower on bovine tooth enamel surface coated with LCFV containing 3 wt% of MPC than in the control treatment (0 wt% MPC). Therefore, this novel LCFV containing a low concentration of MPC (e.g., 3 wt%) would be effective in anti-biofouling while maintaining the important advantageous features of light-curable fluoride in preventing demineralization.